Towards a continuous pilot scale pyrolysis based biorefinery for production of biooil and biochar from sawdust. (1st July 2020) - Soni, Bhavin; Karmee, Sanjib Kumar
Highlights: Effect of temperature was evaluated for batch pyrolysis of sawdust. A pyrolysis based biorefinery approach was developed for valorization of sawdust in a pilot scale. Bio-oil was characterized using FT-IR, NMR ( 1 H and 13 C) and GC–MS. Bio-char was characterized using TGA, FT-IR and SEM. GC analysis was carried out to analyze pyro-gas. Abstract: Sawdust was first pyrolysed in a fixed bed batch scale reactor at temperatures between 400 °C and 600 °C. Optimum temperature for pyrolysis of sawdust was found to be 500 °C; at which, bio-oil (34.9 wt%), bio-char (38.6 wt%) and pyro-gas (26.5 wt%) were obtained. Subsequently, the reaction was scaled-up using a vertical moving bed type continuous reactor (capacity 15 kg/hr) and at 500 °C, the obtained yields of products were 41.05 wt% of bio-oil, 27.59 wt% of bio-char and 31.36 wt% of pyro-gas (mixture of non-condensable gases). Bio-oil was characterized using 1 H and 13 C NMR, FT-IR and GC–MS. GC–MS analysis indicates that 71 chemical compounds are present in bio-oil. The bio-char was characterized using TGA, FT-IR and SEM; these analyses showed that, it is porous in nature and contain negligible amount of volatiles. In addition, the GC analysis of pyro-gas confirms that, different gases viz. H2 (1.59 vol%), N2 (13.61 vol%), O2 (2.48 vol%), CO (54.23 vol%), CH4 (8.02 vol%) and CO2 (24.72 vol%) are present in it. Under optimized reaction condition, during batch pyrolysis, bio-oil yield was 34.9 wt% and bio-char yield was 38.6 wt%; whereas continuous pyrolysis gave 41.05 wt% and 27.59 wt% yields for bio-oil and bio-char respectively.